P.053 Development of an EEG curriculum for icu nurses to facilitate real time screening of continuous EEG data for seizures in critically ill adults. (2nd June 2017) - Kromm, JA; Waechter, J; Kramer, A
Abstract : Background: Nonconvulsive seizures (NCSz) occur commonly in critically ill patients and are harmful. Diagnosis requires detection with continuous electroencephalography (cEEG) that necessitates frequent interpretation by experts. This is often not possible, and requires large amounts of resources. Screening level interpretation of cEEG by ICU nurses to facilitate timely expert diagnosis may be one solution.Methods: Kern's approach to curriculum development was utilized to inform creation of a cEEG curriculum for ICU nurses.Results: A needs assessment revealed 80%, 94%, and 100% of nurses lacked comfort in basic seizure/EEG principles, EEG and CDSA interpretation respectively. The most requested method of learning (76%) involved simulation. A spiral curriculum of 15 interactive online tutorials with corresponding practice/simulation modules providing instant feedback was developed. To evaluate curriculum impact, time spent on modules, improvement in nursing knowledge, and diagnostic accuracy will be evaluated using pre and post curriculum tests. Participant satisfaction will be evaluated using electronic surveys.Conclusions: Development of a curriculum to teach ICU nurses basic screening diagnostic skills for NCSz is possible. Moving forward, we hope to refine and validate this learning tool and formally implement its use to help screen for NCSz prior to expert interpretation.